GAMBARAN KEJADIAN ANEMIA PADA REMAJA PUTRI DI SMA NEGERI KEBAKRAMAT KARANGANYAR - N. Kadek Sri Eka Putri; Hastutik Tutik (Jurnal Ilmiah Maternal, 2022)
Adolescent girls are one of the groups that are prone to anemia. Because at that time they were also menstruating, even more so because of their lack of knowledge about anemia. When young women experience their first menstruation, they need more iron to replace the loss due to menstruation (Hallberg, Rossander-Hulten, 1991). The purpose of this study was to describe the incidence of anemia in adolescent girls about anemia at SMA Negeri Kebakkramat Karanganyar. The research method used is descriptive. The location of the research was carried out at SMA Negeri Kebakkramat Karanganyar, held in March 2022. The sample used in this study was accidental sampling with 35 respondents. Primary data collection is by examining hemoglobin levels in adolescent girls, the assessment of hemoglobin level examination results is divided into mild anemia, moderate anemia, severe anemia and normal/non-anemic (WHO, 2011). To analyze the data using univariate analysis, namely analyzing the existing variables descriptively by calculating the distribution of frequencies and proportions to describe the incidence of anemia. From the results of the study, it was found that most of the respondents had normal hemoglobin levels (94.3%) and a small proportion (5.7%) had mild anemia.